Analysis Business Model Of SMEs Craft Industry In The North Sumatra Province - Samrin (International Journal of Management, Economic and Accounting, 2023)
The aim of this research is to determine and analyze the SWOT formulation of the shell industry business in Provinsi Sumatera Utara. The data processing and analysis methods used were factor tests and discriminant analysis using the Cochran and Kaiser Meyer Olkin Measure of Sampling (KMO) tests. It is hoped that the results of this research can strengthen the results of previous year's research by exploring potential marketing strategies and comparisons of each industry. The formulation of a blue ocean strategy that can be recommended to Provinsi Sumatera Utara Small and Medium Industries (HCI), includes: (1) Through the six paths framework, there are four alternatives that can be used by Provinsi Sumatera Utara SMEs to reconstruct its market boundaries, including looking at alternative industries, strategic groups, complementary product and service offerings, and emotional-functional appeal for buyers. (2) Formulation of a four-step framework by enhancing hospitality and decorum; as well as creating hall or auditorium packages for exhibitions as well as product packages, supporting facilities, promotions via social networks, light visualization concepts, and rental of stands to provide appetizers. (3) Strategy formulation has three good characteristics, namely focusing on service and improving product marketing, divergent with the creation of new factors that can make Provinsi Sumatera Utara SMEs stay away from competition. Formulation Model The competitive strategy for the Shellfish industry is formulated using the SWOT Strategy, namely (1) The appropriate SWOT strategy for Shellfish SMEs in developing their business and facing competition between businesses (commercial studies) is another market penetration strategy that emerges from the QSPM matrix. (2) The factor that is the advantage of the Shell Shell HCI which can be used to increase competitiveness in facing competition between used tire businesses is the cheaper price factor. (3) There are 9 key strategic factors that influence competition between HCI Shellfish and its competitors, these strategic factors are finance, price, operational techniques, operational costs, facilities and infrastructure, promotion and advertising, transportation facilities, service quality, completeness of business operational equipment.